Implementation of the Family-Centered Care Model During Invasive Actions of Giving Injections and Installing Infusions Children's Nurses - Tri Ratnaningsih; Erna Supatmini; Ayu Tri Widiyanti (CV Media Inti Teknologi, 2024)
The aim of implementing Community Service is the implementation of the Family Centered Care Model in the Children's Inpatient Room using invasive injections and infusions at Dr Soetomo Hospital, Surabaya. This community service was carried out at the Children's Inpatient Installation at Dr. RSUD. Soetomo Surabaya consists of 4 rooms. The rooms are the sleeping room, Nakula Sadewa room, Bona 1 room, and Bona 2 room with a total of 92 nurses. The four rooms are children's inpatient rooms that provide low-care nursing care so services with an integrated family-oriented care (FCC) system have not yet been established. The method used in this community service is to involve the family, each nurse will carry out invasive procedures on children with stages of preparation, implementation, and reporting. Implementation results Almost all patient respondents received family-centered care in the good category, 85 people (92.4%). Meanwhile, there were only 7 patients who underwent family-centered care in the sufficient category (7.6%). This shows that patients and nurses at IRNA Children's Hospital Dr. Soetomo Surabaya have implemented a family-centered care system in nursing care and health services.